Oxidative stress in critically ill ventilated adults: effects of vitamin D3 and associations with alveolar macrophage function. Issue 5 (May 2018) - Han, Jenny; Alvarez, Jessica; Staitieh, Bashar; Tangpricha, Vin; Hao, Li; Ziegler, Thomas; Martin, Greg; Brown, Lou
Abstract Background/objectives Disruptions in redox balance lead to oxidative stress, a promoter of morbidity in critical illness. This study aimed to: (1) characterize the plasma and alveolar thiol/disulfide redox pools, (2) examine their associations with alveolar macrophage phagocytosis, and (3) determine the effect of high dose vitamin D3 on plasma thiol/disulfide redox. Subjects/methods Subjects were 30 critically ill, ventilated adults in a double-blind randomized trial of high-dose (250 000 or 500 000 IU) vitamin D3 or placebo. Baseline bronchoalveolar lavage fluid (BALF) samples were analyzed for determination of alveolar phagocytosis index (PI) and for concentrations of glutathione (GSH), glutathione disulfide (GSSG), cysteine (Cys), cystine (CySS), and their respective redox potentials (EhGSSG and EhCySS). Plasma redox outcomes were assessed at baseline and days 7 and 14. Results Baseline plasma Cys was inversely associated with alveolar PI (ρ  = −0.69, P  = 0.003), and Eh CySS was positively associated with PI (ρ  = 0.61, P  = 0.01). Over time, among all subjects there was an increase in plasma GSH levels and a decrease in Eh GSSG (P  < 0.01 for both), with no difference by treatment group. Vitamin D3 decreased oxidized plasma GSSG to a more normal state (P for group x time = 0.009). Conclusions Oxidative stress indicators were positively associated with alveolar macrophage phagocytic function in acutely ill ventilated adults. High-dose vitamin D3 decreased plasma GSSG concentrations, which suggests that vitamin D can possibly improve the oxidative stress environment.